Large scale aspects of the monsoon-2011 Relevant to the objectives of the CTCZ - SIKKA, DR; TOMAR, CS; LASKAR, SI; GOYAL, SUMAN; TYAGI, AJIT (MAUSAM, 2013)
Hkkjr esa xzh"edkyhu ekulwu ds nkSjku flukWfIVd vkSj mi&ekSleh mrkj p<+koksa dks le>us ds fy, o"kZ 2011 esa egk}hih; m".kdfVca/kh; vfHklj.k {ks= ¼lh-Vh-lh-tsM-½ ds uke ls Hkkjrh; ok;qeaMyh;&leqnzh foKku leqnk; us ,d QhYM dk;Zdze vk;ksftr fd;kA bl dk;Zdze dk ,d mís'; ekulwu ds flukWfIVd vkSj varjk&ekSleh mrkj&p<+koksa ls lacaf/kr c`greku ifjlapj.k ds dzfed fodkl ds ckjs esa tkudkjh izkIr djuk Hkh jgk gSA bl 'kks/k i= esa ekulwu 2011 ds le; cM+s iSekus ij gq, mrkj&Pk<+koksa ds ckjs esa Hkh crk;k x;k gSA o"kZ 2011 esa ekuwlu esa ekSle dh yxHkx lkekU; o"kkZ gqbZ rFkkfi mi&ekSleh eku ij twu ekg esa vPNh o"kkZ gqbZ] rRi'pkr tqykbZ ekg esa de o"kkZ gqbZ vksj fQj vxLr ekg ds vkjaHk ls ysdj flracj ekg ds var rd fQj ls vPNh o"kkZ gqbZA ekSle ds iwokZ)Z esa djhc&djhc U;wVªy yk&fuuk fLFkfr;k¡ cuhA rFkkfi vxLr ekg ls ysdj flracj ekg ds var rd Hkwe/;js[kh; iwohZ iz'kkar egklkxj esa leqnz lrg rkieku ¼,l-,l-Vh-½ lkekU; ls de ¼yk&fuuk fLFkfr;k¡½ esa ifjofrZr gks x,A gkykafd xaxk ds eSnkuh Hkkxksa esa fuEu {kksHkeaMy ij leqnz dh rjQ ls vkus okyh ok;q dk izokg cuk] ij iwjh _rq esa ok;q foy; yksM lkekU; ls cgqr de cus jgsA bl 'kks/k i= esa flukWfIVd ds fofHkUu igyq] iz'kkar egklkxj esa ,l-,l-Vh ds lqnwj izHkko ls lacaf/kr ekulwu ds miekSleh mrkj&p<+koksa rFkk Hkkjrh; leqnzh f}/zkqo ¼vkbZ-vks-Mh-½ ds LFkkuh; izHkko ij fopkj&foe'kZ fd;k x;kA blds lkFk&lkFk izpkyukRed lkaf[;dh; ekSle izkxqfDr ¼,u-MCY;w-ih-½ fun'kksZa] ;wjksih; e/; vof/k ekSle iwokZuqeku dsUnz ¼bZ-lh-,e-MCY;w-,Q-½] HkweaMyh; iwokZuqeku iz.kkyh ¼th-,Q-,l-½ vkSj ekSle vuqla/kku vkSj iwokZuqeku ¼MCY;w-vkj-,Q-½ ds fu"iknu ij Hkh fopkj&foe'kZ fd;k x;kA lh-Vh-lh-tsM- vkadM+ksa dk mi;ksx djrs gq, ekulwu 2011 ds fu"iknu ds vk/kj ij vkxs fd, tkus okys vuqla/kku ds dbZ {ks=ksa ds fo"k; esa Hkh lq>ko j[ks x,A Indian atmosphere-ocean science community organised a field programme known as Continental Tropical Convergence Zone (CTCZ) during 2011 to understand the synoptic and sub-seasonal fluctuations of summer monsoon over India. One of the objectives of the programme was to understand the evolution of the large scale circulation in relation to synoptic & intra-seasonal fluctuations of the monsoon. The paper addresses the large scale fluctuations of Monsoon-2011. The Monsoon-2011 performed very close to the normal rainfall of the season. However, on the sub-seasonal scale its performance was good during June, became deficient during July and it recovered from the beginning of August to the end of September. The early part of the season was accompanied by near neutral La-Nina conditions. However, sea surface temperatures (SSTs) in the Equatorial Eastern Pacific Ocean shifted to below normal (La-Nina conditions) from August to the end of September. As the Gangetic Plain was swept by marine origin air stream in the lower troposphere, the aerosol load remained much below the normal during the entire season. The paper discusses different aspect of synoptic, sub-seasonal fluctuations of monsoon in relation to remote forcing of the SSTs in the Pacific and the local forcing of the Indian Ocean Dipole (IOD). Also the performance of the operational numerical weather prediction (NWP) models: European Centre for Medium-Range Weather Forecasts (ECMWF), Global Forecast System (GFS) and Weather Research and Forecasting (WRF) is discussed. Several areas of further research using CTCZ data are also suggested based on the performance of the Monsoon-2011.